1998
DOI: 10.1152/ajplung.1998.275.1.l47
|View full text |Cite
|
Sign up to set email alerts
|

Increased secretion of urokinase-type plasminogen activator by human lung microvascular endothelial cells

Abstract: Human lung microvascular endothelial cells (HLMECs) secreted 1.5–15 times more urokinase-type plasminogen activator (uPA) antigen than human hepatic microvascular endothelial cells, human umbilical vein endothelial cells (HUVECs), angioma endothelial cells, and lung fibroblasts. All of these cells also secreted a 100-fold greater amount of plasminogen activator inhibitor-1 than of uPA antigen, and uPA activities were not detected in the culture medium. The expression of uPA mRNA in HLMECs was higher (100-fold)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
0
30
0
2
Order By: Relevance
“…No significant difference was observed between HUVEC and HPMEC after stimulation with LPS and TNF-␣. Previous studies concerning the secretion of urokinase-type plasminogen activator have already indicated differences between the human lung microvascular endothelium and HUVEC (38). In the bovine lung, TNF-␣ caused different effects on microvascular vs. macrovascular endothelial cell monolayers of the lung (29).…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was observed between HUVEC and HPMEC after stimulation with LPS and TNF-␣. Previous studies concerning the secretion of urokinase-type plasminogen activator have already indicated differences between the human lung microvascular endothelium and HUVEC (38). In the bovine lung, TNF-␣ caused different effects on microvascular vs. macrovascular endothelial cell monolayers of the lung (29).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial fraction of total plasminogen activator activity in the lungs is generated within the alveolar space (38,46). The pulmonary vasculature also expresses plasminogen activators (28,49). Thus the lungs seem to be well equipped to function as blood filters that trap and dissolve emboli (12).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial products, such as endotoxin, as well as proinflammatory cytokines, including IL-1␤ and TNF-␣, whose release is increased in the setting of severe infection, induce uPA expression and secretion (5,6,15,23). Cleavage of cell-bound plasminogen to plasmin by uPA, in addition to promoting fibrinolysis, can enhance release of proinflammatory mediators, including cytokines such as IL-1␤ or matrix metalloproteinases, by facilitating conversion of the pro-form to the biologically active molecules, thereby potentiating acute inflammatory reactions (15,24).…”
Section: U Rokinase Plasminogen Activator (Upa)mentioning
confidence: 99%